You know that

*a*(

*b*-

*a*) = 0, which means either

*a*= 0,

*b*-

*a*= 0, or both. (You know this because when a product equals zero, that can only happen when at least one of the things being multiplied together is zero.)

Since we're given

*a*>

*b*, we know

*b*-

*a*

__can't be__zero. So

*a*

__has to be__0. The other two conditions follow from that:

I

*a*= 0 (we know this is true)

II

*b*< 0 (we know this is true because

*a*= 0, and

*b*is less than

*a*)

III

*a*-

*b*> 0 (we know this is true because 0 - a negative number will always be positive)

nice

ReplyDeleteThis comment has been removed by a blog administrator.

ReplyDelete